Improving Cognitive Abilities Of Group A Children Through Number Cards At Uswatun Hasanah Paud In The 2024/2025 Academic Year - Nurjannah, Nurjannah; Arzani, M.; Taufik, M. (JUPE : Jurnal Pendidikan Mandala, 2025)
Abstract This study aims to improve children's self-regulation in group B through clog outbound games at Paud Abata Ceria. The method used in this research is classroom action research (PTK) using two cycles. Each cycle consists of planning, implementation, observation and reflection, the research subjects were 8 children in group B. Data was collected through observation and documentation. Then analyzed qualitatively and quantitatively. The results showed an increase in children's self-regulation abilities such as emotional control, cooperation behavior and independence. In cycle I, the percentage of success reached 62.5% because there were 5 children who were complete and 3 children who were not complete and increased to 87.5% in cycle II, namely 7 children who were complete while 1 child was not complete. So the conclusion is that clog outbound games are effective in improving early childhood self-regulation.